Authority's board of directors resolution No. 92 of the year 2014 on amending the authority's board of directors resolution No. 66/2009 regarding the development fee levied on the companies subject to the authority's supervision The Egyptian financial supervisory authority ; translated by The middle east library for economic services. - The Egyptian financial supervisory authority; The middle east library for economic services, translator. (2025)
Egyptian financial supervisory authority authority’s board of directors resolutions no. 92 of the year 2014 dated 9/6/2014 on amending the authority’s board of directors resolutions no.66/2009 regarding the development fee levied on the companies subject to the authority’s supervision الهيئة العامة للرقابة المالية قرار مجلس إدارة الهيئة رقم 92 لسنة 2014 بتعديل قرار مجلس إدارة الهيئة رقم 66 لسنة 2009 بشان رسم التطوير المقرر على الشركات الخاضعة لرقابة الهيئة